O povoamento calcolítico do alvéolo de Vila Chã, Esposende (Norte de Portugal) : notas a propósito das escavações arqueológicaas de Bitarandos - Bettencourt, Ana; Dinis, António; Cruz, Carlos; Silva, Isabel Sousa e (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
This article draws upon the recent archaeological excavations at the site of Bitarados (Esposende). This site was disturbed by urban development in the eighties. The earthworks uncovered important archaeological finds, wich are kept in the Museu Municipal de Esposende. The excavations, integrated in the project The Entre-Douro-e-Minho landscape since middle of III to the end of II millenium BC revealed an open settlement site with different occupations dating to the Calcolitic period.